2012
DOI: 10.1158/1078-0432.ccr-12-1683
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Liver Iron Content Predicts for Nonrelapse Mortality in MDS and AML Patients Undergoing Allogeneic Stem Cell Transplantation

Abstract: Purpose: Retrospective, surrogate marker-based studies have found inconsistent associations between systemic iron overload (SIO) and adverse outcome in patients undergoing allogeneic stem cell transplantation (allo-SCT). As a consequence, the impact of SIO in this context remains under debate. The aim of this study was to test whether the objective pretransplant quantification of liver-iron content (LIC) by magnetic resonance imaging (MRI) could circumvent these limitations and conclusively define the prognost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 30 publications
7
43
1
Order By: Relevance
“…Several prospective studies and a multi-center meta-analysis examining the impact of elevated LIC on HSCT outcomes came to different conclusions regarding the prognostic relevance of LIC in HSCT, mainly due to the use of different LIC thresholds. [17][18][19][20][21] However, an LIC threshold of over 7 mg Fe/g dw has been associated with a decrease in overall survival and non-relapse mortality. 19,20 In the meta-analysis performed by Armand, …”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies and a multi-center meta-analysis examining the impact of elevated LIC on HSCT outcomes came to different conclusions regarding the prognostic relevance of LIC in HSCT, mainly due to the use of different LIC thresholds. [17][18][19][20][21] However, an LIC threshold of over 7 mg Fe/g dw has been associated with a decrease in overall survival and non-relapse mortality. 19,20 In the meta-analysis performed by Armand, …”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated pretransplantation serum ferritin levels were found to be associated with lower survival rates in patients with MDS who underwent allogeneic SCT, suggesting that iron overload may affect transplantation outcome for patients with MDS, as it does in thalassemia. [254][255][256][257][258][259] Several studies have investigated the use of iron-chelating agents in MDS patients with transfusion-dependent anemia. A report on MDS patients receiving desferrioxamine as a continuous, subcutaneous 12-hour infusion by pump found that this chelating agent induced effective iron depletion in a significant proportion of patients.…”
mentioning
confidence: 99%
“…serum TS plus ferritin and/or radiological tests and/or liver biopsy) to define iron overload. 1,2,3,8,12 Some of them found a relationship between iron overload and post-transplant survival. 2,3 On the other hand some others did not.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,8,12 Some of them found a relationship between iron overload and post-transplant survival. 2,3 On the other hand some others did not. 1,12 Interestingly the relationship between iron overload and VOD, probably the most expected specific transplant complication in patients with liver injury, was not reported in any of these studies considered to have adequate methodologies for detection of iron overload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation